Pay-Based Gender Discrimination in Private School: Four Cases of Kathmandu, Nepal - Khatri, Binda (Dhaulagiri Journal of Sociology and Anthropology, 2022)
Unfair treatment based on sex is considered gender discrimination. Gender discrimination in the workplace has always existed, and the pay gap is a prominent topic worldwide. This paper investigates and provides information on the condition of the pay gap in private schools in Kathmandu valley. Four private schools in Bansbari, Kathmandu, were selected for the research. Out of 139 teachers at the selected schools, 28 female and 20 male teachers were selected for this research using the snowball sampling method. A questionnaire was administered to gather information. The open code analysis of the open-ended questionnaire showed that there was inequality in salary distribution. Remuneration differed not only by employees' working hours and qualifications but also by gender. This paper discusses how gender biases are prevalent in academia.